1999
DOI: 10.1345/aph.18317
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, Clinical Correlation, and Patient Acceptance of Two Handheld Prothrombin Time Monitoring Devices in the Ambulatory Setting

Abstract: The Coaguchek was superior to the ProTime Microcoagulation System in accuracy, clinical correlation, and ease of use. The study also showed that patients preferred capillary blood sampling by finger puncture over venipuncture for INR monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 20 publications
1
21
1
Order By: Relevance
“…If all Coaguchek S™ device measurements above 3.5 INR were repeated in the central laboratory this value would drop to 10%. This value agrees with the study published by Chapman and associates 20 where an 8% margin of error was found for medical decisions based on the Coaguchek™ system.…”
Section: Discussionsupporting
confidence: 92%
“…If all Coaguchek S™ device measurements above 3.5 INR were repeated in the central laboratory this value would drop to 10%. This value agrees with the study published by Chapman and associates 20 where an 8% margin of error was found for medical decisions based on the Coaguchek™ system.…”
Section: Discussionsupporting
confidence: 92%
“…It is not rational to use the POC devices for routine INR monitoring because it may cause tromboembolic events result- ing from lower doses of warfarin therapy according to false high levels of INR. The ProTime monitor has been shown to correlate well with laboratory testing of INR with correlation coefficients on the order of 86-93% in some studies [7][8][9][10] whereas some studies explain the poor INR correlation between various POC systems and laboratory methods [8;9]. Similarly, the results of our study, do not correlate between POC devices and central laboratory results especially INR values greater than 2.0.…”
Section: Discussioncontrasting
confidence: 40%
“…Of all the conducted measurement the dosage of VKA would have to be changed in 8.0-25% of the cases due to the inaccuracy of the CoaguChek R coagulometer [59,71,72,80,81]. Many of the studies displayed in Table 3 have not used optimal designs, e.g.…”
Section: Measurement Of Inrmentioning
confidence: 99%